Ca2+ Regulates Dimerization of the BAR Domain Protein PICK1 and Consequent Membrane Curvature - Stan, Georgiana F.; Shoemark, Deborah K.; Alibhai, Dominic; Hanley, Jonathan G. (Frontiers in Molecular Neuroscience, 2022)
BAR domain proteins are critical regulators of membrane geometry. They induce and stabilize membrane curvature for processes such as clathrin-coated pit formation and endosomal membrane tubulation. BAR domains form their characteristic crescent shaped structure when in the dimeric form, indicating that the formation of the dimer is critical to their function of inducing membrane curvature, and suggesting that a dynamic monomer:dimer equilibrium regulated by cellular signalling would be a powerful mechanism for controlling BAR domain protein function. However, to our knowledge, cellular mechanisms for regulating BAR domain dimerisation remain unexplored. PICK1 is a Ca2+-binding BAR domain protein involved in the endocytosis and endosomal recycling of neuronal AMPA receptors and other transmembrane proteins. Here, we demonstrate that PICK1 dimerisation is regulated by a direct effect of Ca2+ ions via acidic regions in the BAR domain and at the N-terminus. While cellular membrane tubulating activity of PICK1 is absent under basal conditions, Ca2+ influx causes the generation of membrane tubules that originate from the cell surface. Furthermore, in neurons, PICK1 dimerisation increases transiently following NMDA receptor stimulation. We believe that this novel mechanism for regulating BAR domain dimerisation and function represents a significant conceptual advance in our knowledge about the regulation of cellular membrane curvature.